Nonlinear discrete light propagation in photonic liquid crystal fibers - Rutkowska, Katarzyna Agnieszka; Laudyn, Urszula; Jung, Paweł (Photonics Letters of Poland, 2013)
In this report, the results of numerical simulations describing (discrete) light propagation in photonic liquid crystal fibers (PLCFs) are presented. Specifically, the deviation in the spatial broadening of the beams characterized by different initial widths is analyzed. In this context, particular attention is devoted to the cases in which thermal (optical) nonlinearity in liquid crystals (LCs) is taken into account. Spatial light localization and/or delocalization are demonstrated, with the final scenario determined by the initial width and amplitude of the light beam. In particular, possibility of the discrete soliton generation is demonstrated. A qualitative comparison with experimental data obtained in analogous conditions (with use of specific PLCF samples) is also made. Full Text: PDF References P. St. J. Russell, "Photonic Crystal Fibers", Science 299, 358 (2003). CrossRef E. Poli, A.Cucinotta, S. Selleri, Photonic Crystal Fibers. Properties and Applications (Springer, The Netherlands 2007). T.R. Woliński et al., "Emerging photonic devices based on photonic liquid crystal fibers", Phot. Lett. Poland 3(1), 20 (2011). CrossRef I-C. Khoo, S-T. Wu, Optics and Nonlinear Optics of Liquid Crystals (World Scientific Pub., Singapore 1993). CrossRef J. Schirmer et al., "Birefringence and Refractive Indices Dispersion of Different Liquid Crystalline Structures", Mol. Cryst. Liq. Cryst. 307(1), 17 (1997). CrossRef J. Fleischer, M. Segev, N. Efremidis, D. Christodoulides, "Observation of two-dimensional discrete solitons in optically induced nonlinear photonic lattices", Nature 422, 147 (2003). CrossRef F. Lederer, Y. Silberberg, "Discrete Solitons", Opt. Photon. News 2, 48 (2002). CrossRef A. Szameit, D. Blömer, "Hexagonal waveguide arrays written with fs-laser pulses", J. Burghoff, Appl. Phys. B 82, 507 (2006). CrossRef K.A. Rutkowska, K. Orzechowski, "Discrete light propagation in microstructured fibers infiltrated with liquid crystals", Proc. SPIE 8697, 86971F (2012). CrossRef M.S. Chychłowski et al., "Photo-Induced Orientation of Nematic Liquid Crystals in Microcapillaries", Acta Phys. Pol. A, 118, 1100 (2010). DirectLink